Consumption and feeding preference of Echinogammarus marinus on two different algae: fucus vesiculosus and Ulva intestinalis - Martins, Irene (2014)
Echinogammarus marinus constitutes the most abundant amphipod species in Fucus spp. assemblages from many North Atlantic estuaries. However, there are some doubts about the real use of fucoids by the amphipod. Whilst some studies report the ingestion of Fucus vesiculosus by E. marinus, others suggest that the amphipod preference for fucoids is mostly related to sheltering rather than feeding, due to the high phlorotannin content of brown algae. The purpose of the present work was to disentangle this issue by checking the consumption rate and feeding preference of E. marinus on F. vesiculosus, its preferential habitat, and on Ulva intestinalis, a green algae abundant in the Mondego estuary (Western Coast of Portugal) and usually considered as highly palatable for herbivores. In a 2-stage laboratorial setup, fresh disks of the two types of algae were offered to E. marinus for three days. Consumption rates were estimated from differences between algal and animal initial and final fresh weights using a control correction factor, while preference was tested by differences in algal consumption rates when no choice was offered (stage 1) and when the two algae were offered simultaneously (stage 2). Results showed that E. marinus effectively consumed fresh F. vesiculosus in much higher amounts than U. intestinalis and significantly preferred to consume F. vesiculosus over U. intestinalis. Therefore, feeding habits must be one of the factors related to the close association of the amphipod with F. vesiculosus, although other factors may also be involved (e.g. sheltering).